# How do I solve 6 3/4 + 1 5/6?

mwestwood | Certified Educator

calendarEducator since 2006

starTop subjects are Literature, History, and Social Sciences

This is probably the old-fashioned way, but, perhaps, it may be simpler:

Another way to solve this problem is just to find the lowest common denominator for the fractions as they are without converting the mixed number to an improper fraction.

The lowest common denominator for 4 and 6 is 12 as 4 goes into 12  3 times and 6 goes into 12  2 times.

(The entire section contains 2 answers and 212 words.)

check Approved by eNotes Editorial

pohnpei397 | Certified Educator

calendarEducator since 2009

starTop subjects are History, Literature, and Social Sciences

check Approved by eNotes Editorial

malkaam | Student

6 3/4 + 1 5/6

In order to solve this you need to change the whole numbers to fractions, this is how you change them: 6 3/4 = multiply the denominator by the whole number and then add the numerator your fraction will become 27/4, and in order to change it decimal just divide 3 by 4 and take the whole number in units place, it will then become 6.75. Same process will then be applied to 1 5/6 and it will become 11/6, decimal= 1.83.

therefore,

27/4 + 11/6

3(27/4) + 2(11/6)                             (find the LCM, which in this case is 12)

81/12 + 22/12

81+22/12

103/12

Or you can also you a calculator.

check Approved by eNotes Editorial
jess1999 | Student

6 3/4 + 1 5/6

First let's add the fraction ( 3/4 and 5/6 )

By adding the fraction you should get

38/24 now change this to a mixed number

By changing the improper fraction to a mixed number, you should get

1 7/12 now add this with 6 and 1

check Approved by eNotes Editorial
parama9000 | Student

6 3/4=6x4+3/4=27/4

Similarly, 1 5/6=11/6

27/4=81/12

11/6=22/12

81/12+22/12=103/12=8 7/12

acompanioninthetardis | Student

6 3/4 plus 1 5/6 so basically you first turn both into unsimplified fractions. So 27/4 and 11/6. Then you want to try to get a similar denominator or bottom part of the fraction. Both 4 and 6 have a least common denominator of 12 so 12 is your new denominator now hold this thought. You have to multiply 6 by 2 to get 12 so whatever you do to the bottom you do to the top. So it would be 22/12 and you need to multiply 4 by three so 81/12. Then you add 22 and 108 to get 103/12 and then just simplify to 8 7/12.

zumba96 | Student

Change it into a mixed number

# 6 3/4 + 1 5/6

27/4+11/6

Find the LCM

162/24 +44/24

206/24

8 7/12

check Approved by eNotes Editorial
atyourservice | Student

`6 3/4 + 1 5/6`

`4/4 xx 6/1 = 24/4 +3/4 = 27/4`

`6/6= 1`

`6/6 + 5/6 =11/6`

`27/4 + 11/6`

the denominators have a common multiple of 12 so multiply to get the denominators to equal 24

`27/4 xx 3 = 81/12`

`11/6 xx 2 = 22/12`

`81/12 + 22/12 = 103/12`

the answer is `103/12 ` but you can try to simplify it

12 goes into 103,  8 times which is 96

`103- 96 = 7` so seven is left over

check Approved by eNotes Editorial
princessenotes | Student

First, you need the denominator to be the same.

24/4 + 3/4 = 27/4

11/6

6 3/4 + 1 5/6 = 27/4 + 11/6 = (12/12)*(27/4 + 11/6)

= (3*27)/12 + (2*11)/12 = (81 + 22)/12 = 103/12

= 96/12 + 7/12 = 8 + 7/12 = 8 7/12

check Approved by eNotes Editorial
amitparmar | Student

solve 63/4+ 15/6,

we may written as

63/4=15.75...............<1>

we may also written as

15/6=2.5..................<2>

for solving this question adding both equation

63/4+ 15/6=2.5+15.75

or,63/4+ 15/6=18.25

check Approved by eNotes Editorial
neela | Student

How do I solve 6 3/4 + 1 5/6?

Solution:

6 3/4 + 1 5/6?

As in algebra (where we group like terms), here, you can group whole numbers together.

Therefore, 6  3/4 + 1  5/6 = 6+3/4+1+5/6

= 6+1+3/4+1/6 , by commutative law.

=7  + (3/4+5/6).......................(1)

Fraction could be added by converting the  fractions into equivalent fractions with common dinominators.The common dinominator, here, for 4 and 6 is their LCM, that is ,12. So equivalent fraction of 3/4 with 12 as dinaminator is 3*3/(4*3) and that of 5/6=5*2/(6*2) . So , the expression at  (1) could now be rewritten like:

7 +  3*3/(4*3)+(5*2/(6*2)

=7 + 9/12+10/12

=7+(9+10)/12

=7 + 19/12

=7  + 1 + (19-12)/12

=8 + 7/12. Whole numbers added.

=8  7/12

check Approved by eNotes Editorial
krishna-agrawala | Student

The number 6 3/4 really is equal to 6 + 3/4. It can be rewritten as:

24/4 + 3/4 = 27/4

Similarly 1 5/6 = 1 + 5/6 = 6/6 + 5/6 = 11/6

Therefor:

6 3/4 + 1 5/6 = 27/4 + 11/6 = (12/12)*(27/4 + 11/6)

= (3*27)/12 + (2*11)/12 = (81 + 22)/12 = 103/12

= 96/12 + 7/12 = 8 + 7/12 = 8 7/12

check Approved by eNotes Editorial